Pengembangan usaha kelompok perempuan pengolahan herbal (rempah) melalui pelatihan pengemasan dan pelabelan di Koperasi Simpan Usaha (KSU) Munyai Mekhawan, Pekon Labuhan Mandi, Pesisir Barat, Lampung (Business development of herbal processing women's group through packaging and labeling training in Munyai Mekhawan Small Business Cooperatives (KSU), Labuhan Mandi Village, Pesisir Barat, Lampung) - Riadi, Septa; Saleh, Khairul; Kuswarak, K; Azriya, Niar; Nuraeni, N (Buletin Pengabdian, 2022)
This community service aims to carry out a business assistance program for women's groups at the Munyai Mekhawan Village Savings and Business Cooperative (KSU) in Labuhan Mandi Village, Pesisir Barat Regency, Lampung Province. The community service program is carried out through a mentoring method organized by the Faculty of Economics, Sang Bumi Ruwa Jurai University, with the target of KSU Munyai Mekhawan members, Labuhan Mandi Village. The contribution given is in the form of making herbal medicines for women's herbal processing business groups (spices) in the form of packaging and labeling training activities. The results of the service activities showed that the implementation of the training received a positive and high enthusiasm response from the KSU Munyai Mekhawan member group due to the increased knowledge possessed by the business group, which has the potential to be developed and become additional household income. In conclusion, these activities can increase the knowledge possessed by business groups and have the potential to be developed and become additional household income. Based on the activities carried out, the servant hopes that there will be other community service programs that can increase people's revenue through household businesses.